2011
DOI: 10.1002/pros.22461
|View full text |Cite
|
Sign up to set email alerts
|

AIM1 promoter hypermethylation as a predictor of decreased risk of recurrence following radical prostatectomy

Abstract: Purpose To evaluate the prognostic significance of six epigenetic biomarkers (AIM1, CDH1, KIF1A, MT1G, PAK3 and RBM6 promoter hypermethlation) in a homogeneous group of prostate cancer patients, following radical prostatectomy. Patients and Methods Biomarker analyses were performed retrospectively on tumors from 95 prostate cancer patients all with a Gleason score of 3+4=7 and a minimum follow up period of 8 years. Using Quantitative Methylation Specific PCR (QMSP), we analyzed the promoter region of six gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In the study by Tokumaru et al [26] PGP9.5 was found to have a high frequency of PH in a large panel of primary tumors, and their data support the notion that this gene is a TSG that is inactivated by PH or gene deletion in several types of human cancers. Some genes were described as hypermethylated in other cancer types, these include SSBP2 , [27], CCNA1 [28], [29], AIM1 [30], VGF [17], FKBP4 [31], and we decided to evaluate their promoter methylation status in ovarian tissues samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Tokumaru et al [26] PGP9.5 was found to have a high frequency of PH in a large panel of primary tumors, and their data support the notion that this gene is a TSG that is inactivated by PH or gene deletion in several types of human cancers. Some genes were described as hypermethylated in other cancer types, these include SSBP2 , [27], CCNA1 [28], [29], AIM1 [30], VGF [17], FKBP4 [31], and we decided to evaluate their promoter methylation status in ovarian tissues samples.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, other variable DNA methylation alterations in neoplastic tissue samples have been also associated with the prediction of PSA recurrence after RP [10,17,18,19,20,21,22,23,24]. These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,21,25,26 Our group recently reported that decreased promoter methylation of AIM1 in PCa was associated with shorter time to progression in a cohort of 95 patients with only Gleason sum 3 + 4 = 7. 27 None of these genes were significantly associated with PCa recurrence in the current study in part due to tumor heterogeneity and other associated factors, such as the methylation analysis technique, environmental and endogenous factors, and, as mentioned, population size and heterogeneity.…”
Section: Discussionmentioning
confidence: 54%